Stability analysis of smart grid management system on campus building - Dina Maizana; Ahmad Rezky; Syarifah Muthia Putri; Habib Satria; Moranain Mungkin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Medan Area University is one of the private universities in North Sumatra that is also involved in the development of renewable energy technology. This technological development has initiated the University's efforts to develop an electrical system by developing a smart grid system in order to reduce the University's operational costs. However, in its realization, it has its own challenges, such as power flow stability and transient stability. Both problems can be analyzed using ETAP 12.6 software. In one of the cases analyzed, the smart grid system can reduce the use of the active power of the transformer by 11 kW and a current of 19.7 Amp. Meanwhile, in the Indonesian State Electricity Company (PLN) off condition, the smart grid system has not been able to supply the load because the availability of renewable energy sources is not sufficient for the load requirement. As well as the results of the voltage and frequency analysis, the highest voltage is 376.4 Volts, the lowest is 375.9 Volts, which is still in the stable category of 380 Volt voltage deviation because it is not +5% and -10%, and the overall frequency of the cases discussed is consistent stable at nominal 50 Hz.